Formulasi Sistem Pembuktian Terbalik Tindak Pidana Korupsi di Indonesia dalam Perspektif Hukum Islam - Suaidi (UNIVERSITAS BONDOWOSO, 2021)
Corruption have widespread and even became a culture of Indonesia that the government set up a new system, known as Reversal Burden Of Proof. Even though the model is considered to be contrary to the fundamental principle of the rule of law, but in Islamic law and the evidence, it is legally seen as a necessity to eradicating corruption. It is based on the demands and the welfare of Reversal Burden Of Proof Formulation.